Penerapan Ice Breaking untuk Meningkatkan Motivasi Belajar Siswa Kelas I A UPTD SDN 66 Kanjitongan Kabupaten Maros - Ashar Ashar; Siti Asmawar; Muh. Akmal Hamid; Nurhikma R.; Difa Nadiah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Students are less motivated in the learning process. This study aims to observe the application of ice breaking to increase student learning motivation in class I A UPTD SDN 66 Kanjitongan Maros Regency. The research was conducted using the classroom action research (PTK) method with two cycles, each cycle consisting of three meetings consisting of 27 students (13 boys and 14 girls). Each meeting was carried out with four stages, namely planning, acting, observing, and reflecting. The results showed that student learning motivation in cycle I, obtained 66.67%, and increased in cycle II to 81.48%. Therefore, the application of ice breaking can increase student learning motivation in class I A UPTD SDN 66 Kanjitongan Maros Regency.